THE EFFECT OF LIFE REVIEW THERAPY AND COGNITIFE BEHAVIOR THERAPY (CBT) ON REDUCING STRESS LEVELS IN TRESNA WERDHA NURSING HOME GORONTALO - Rini Fahriani Zees (LP2M Universitas Bina Mandiri Gorontalo, 2019)
Stress was a reaction of a person's condition where desires or demands are not balanced with expectations that caused mental tension and other negative effects such as dizziness, high blood pressure, irritability, sadness, difficulty concentrating, appetite changes, sleeplessness (Niken, 2014). Stress management can be solved through pharmacological and non-pharmacological therapy. One type of non-pharmacological therapy was life review and cognitive behavior therapy. This study aims to determine the effect of life review and CBT therapy on reducing stress levels in the elderly. Research design using experiments approach with one group pre-post test design. 20 respondent was taken through purposive sampling method from 35 respondents . The results showed that there was significant difference between life review therapy and CBT in reducing stress with p value = 0.001. From the result, it can be suggested to all of the nursing home to implemented life review and cognitive behavioral therapy to reduce stress level, especially for elderly.